Homogeneity of parasite assemblages of Dules auriga (Serranidae) in hydrographically heterogeneous sites - Braicovich, Paola Elizabeth (2015)
Parasite assemblages of Dules auriga are described for the first time from samples caught during research cruises in two localities of the Argentine-Uruguayan Common Fishing Zone (AUCFZ) and are compared with four additional samples collected by commercial catches from the same region. A total of 178 fish were examined and 13 parasite species were found. This showed low species richness, a condition observed in some other small benthic species at a low trophic level. The composition of the parasite fauna was similar to those found on other host species in the region, sharing the same set of dominant species with other sympatric fishes, which have been identified as both typical and as indicators of this ecoregion: Grillotia carvajalregorum, Corynosoma australe and Hysterothylacium sp. Multivariate similarity analyses at the infracommunity and the component community levels indicated that the two samples caught at different latitudes in the AUCFZ display almost identical parasite assemblages. This repeatability in assemblage structure was also observed across samples from commercial catches. The homogeneity of the parasite assemblages is considered to be an intrinsic property of fish inhabiting the AUCFZ, independent of their ecology and trophic level.